ANP and BNP plasma levels in patients with rheumatic mitral stenosis after percutaneous balloon mitral valvuloplasty - Mazurkiewicz, Łukasz; Rużyłło, Witold; Chmielak, Zbigniew; Opalińska-Ciszek, Ewa; Janas, Jadwiga; Hoffman, Piotr; Hryniewiecki, Tomasz; Grzybowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Atrial (ANP) and B-type (BNP) natriuretic peptides are hormones secreted by the heart as a response to volume expansion and pressure overload. Aim: To assess the changes of ANP and BNP after percutaneous balloon mitral valvuloplasty (PBMV) and to investigate factors associated with endpoints. Material and methods: The study included 96 patients (90.7% females, age 51.6 ±12.2 years) with rheumatic mitral valve stenosis (mitral valve area (MVA) 1.18 (1.01–1.33) cm2, mean mitral gradient (MMG) 8.2 (7.1–9.2) mm Hg, NYHA 2.09 (1.9–2.5)). Patients were followed up for 29.1 months for the search of endpoints. Results : The PBMV was successful in all cases. After the procedure MVA increased (1.18–1.78 cm2, p < 0.01) and pulmonary capillary wedge pressure (PCWP) decreased (29.8–21.8 mm Hg, p < 0.01). Concentration of ANP significantly rose 30 min after the PBMV (79.2 vs. 134.2 pg/ml, p = 0.012) and dropped significantly after 24 h (134.2 vs. 70.4 pg/ml, p = 0.01). Furthermore, after 36 months concentration of ANP did not differ from the baseline value (p = NS). BNP concentration at day 1 was lower than at baseline (94.5 vs. 80.2 pg/ml, p = 0.032). Moreover, during the follow-up period BNP continued to fall at all time points. In univariate analysis parameters associated with endpoint occurrence were baseline PAP (p = 0.023), baseline PCWP (p = 0.022), baseline NYHA (p = 0.041) and increase in 6-minute walk test (6MWT) (p = 0.043). In multivariate analysis the only factor associated with endpoint occurrence was baseline NYHA (HR = 1.52, 95% CI: –1.3–1.91, p = 0.022). Conclusions : Patients with MS had increased levels of both BNP and ANP. Baseline NYHA class was found to be associated with outcomes after the procedure.